THE SELF-REGULATION ABILITY OF FUTURE MUSIC TEACHERS': STUDENTS' INSIGHTS (Proceedings of the International Conference on Future of Education, 2022)
With the continuous progress and development of society, people's pursuit of life is no longer limited to material pursuit, more and more people begin to yearn for high quality spiritual life. Music as an important part of the art category, the audience in the world is increasing. Music education provides a professional foundation for the spread of music. As the inheritor of music art, future music teachers, that is, music education students, shoulder the important task of laying the foundation of music and exploring the cultivation of outstanding art talents. At the same time, they also face the challenge of how to better improve their professional quality. In order to improve the professional level of music education students, schools provide them with various training and practical activities. In the face of national, social and future students and other different aspects of pressure, it is particularly important for future music teachers to do a good job of self-regulation. This questionnaire will take the music education students as the survey object, through consulting various materials, summarizes the current training projects and contents provided by China and Lithuania for music education students, and formulates a semi-structured interview questionnaire of qualitative research. In the case of collecting the questionnaire and ensuring that the questionnaire meets the needs, this paper discusses the situation of self-regulation in the training of music students in school through qualitative analysis, and puts forward some suggestions and methods of self-regulation from the aspects of system and individual.
Keywords: self-regulation; future music teachers; training; stage fright